TRANSIENT NON-THERMAL MOBILITY OF CO FOR CO-NO CATALYTIC REACTION ON HEXAGONAL LATTICE: A COMPUTER SIMULATION STUDY - Qaisrani, A. U.; Khalid, M.; Chohan, Q. N. (The Nucleus, 2010)
Monte Carlo simulation has been used to study the effect of precursor mechanism along with diffusion of N on a hexagonal lattice for CO-NO heterogeneous catalytic reaction. The reactive window gets enhanced due to the precursor mechanism. It has been also found that the diffusion of N slightly shifts the first order transition (y2) toward higher concentration of CO and therefore by including the diffusion of N the reactive window gets wider. It is observed that whenever precursor mechanism is introduced, the production of CO2 and N2 starts as soon as the CO partial pressure (yCO) departs from zero. The reactive window and production rate increases by increasing the range of precursor mobility.